Impact of Workplace Violence, Bullying and Harassment on the Performance of Female Staff Nurses: A Case Study of Private Sector Hospitals of Hyderabad District, Sindh, Pakistan - Muhammad Bakhsh Lolai; Shuja Ahmed Mahesar; Misbah Bibi Qureshi; Ameer Ali Abro (Journal of Management Practices, Humanities and Social Sciences, 2023)
This paper aims to analyse the impact of workplace violence, bullying, and harassment on the performance of female staff nurses. The main argument of this study is that these issues negatively affect the performance of nurses. The hypothesis of this study is to investigate the impact of the elimination of workplace violence, bullying, and harassment to increase the job performance of nurses. It also explores the causes of growing insecurity and harassment in the workplace and suggests proposals to overcome these hurdles. The paper also suggests the measures that can be taken by hospital management to reduce the risk of bullying and harassment affecting the morale of nurses. It has been argued that the elimination of these problems can significantly contribute to the improvement of workplace culture.For this research, a descriptive cross-sectional study was conducted from the nurses of private sector hospitals located in the Hyderabad district. Convenience sampling techniques were used. The sample size consisted of 127 nurses out of 222 nurses which is 57% of the total population of nurses. Data were collected through a self-structured questionnaire to explore the impact of workplace violence, bullying, and harassment on the performance of female staff nurses.The findings of the study indicate that bullying and harassment have a detrimental effect on the performance of nurses. Additionally, a significant proportion of nurses reported being unable to report such incidents to the appropriate authorities.The significance of the study lies in the relationship between the nurses' (and their co-workers’) experiences in the workplace, the difficulties they face, and the factors that contribute to their stress levels and morale fall. The study has highlighted the problems faced by professional nurses who are working in private hospitals and has drawn attention to formulating recommendations to cope with these issues. The results of this study would make it possible for the health department of Sindh to enhance employee work performance and how much organizational ethics can contribute.